Formative and Validation Human Factors studies of a new disposable autoinjector for subcutaneous delivery of chronic disease therapies. (2nd November 2021) - Lageat, Claire; Combedazou, Anne; Ramus, Claire; Guerrero, Karen; Frolet, Cecile; Glezer, Stanislav
ABSTRACT: Background: Use-related risks related to autoinjector devices have been previously identified. To minimize these problems, the identification of potential use errors is a critical task during device development. Methods: This article presents iterative human factor studies, which aim to assess user interaction with the tested push-on-skin BD Intevia™ 1 mL Disposable Autoinjector, across a wide range of indications, and a broad user population. Results: Through the different human factor studies, use errors were recorded when the participants completed the critical tasks, but their occurrence continuously decreased. First, the incidence of use errors was reduced when the participants read the IFU. In addition, the IFU updates and design change implemented contributed to improve the usability performance. During the validation study, some use errors were still observed, mainly during the first uses. Nevertheless, providing a training to the participants almost fully eliminated the remaining use errors. Conclusion: Thus, these results demonstrated that this new autoinjector can be safely and efficiently used for its intended uses and under the expected use conditions by all tested user groups.